A path model of smoking behaviour among senior high school students in Taiwan. (February 2016) - Chen, Yi-Chun; Huang, Hui-Wen; Cheng, Chung-Ping; Hsieh, Hsin-Chin; Huang, Chih-Ling
Objective: The purpose of this study was to explore the ways in which social smoking expectations mediate the relationship between adolescent smoking behaviour and the smoking behaviour of family and peers. Design: Descriptive, cross-sectional survey. Setting: Taiwan, Republic of China. Method: The participants were 921 senior high school students who completed a questionnaire to measure smoking status, family and peer smoking and social smoking expectations. The survey was conducted from November to December in 2009. Structural equation modelling was performed to test a mediation model. Analysis was performed using PRELIS 2 and LISREL 8.7 software. Results: After adjusting for students' gender, age and school type, it is clear that social expectations mediate the relationship between sibling smoking, peer smoking and adolescent smoking. The path coefficients of sibling and peer smoking on social expectations in the mediator model were moderate, β = .15–.41, p  < .05, but the coefficient of social expectations on adolescent smoking was strong, β = .95, p  < .001. The total indirect effects between exogenous latent variables and adolescent smoking were .54, indicating a strong association that, in this model, is explained by the mediation of social expectations. Conclusion: Determining the mechanisms that influence adolescent smoking is of scientific interest because knowledge of these mechanisms is a prerequisite for the development of recommendations aimed at prevention. With this knowledge, health professionals can develop smoking-prevention policies and education programmes based on reducing the mediating effect of social smoking expectations on the relationship of family smoking and peer smoking with adolescent smoking.